USE OF ESSENTIAL OIL, AROMATIC, AND MEDICINAL PLANTS IN GREEN SPACE DESIGN - Savchuk, Kateryna; Gnatiuk, Liliia (Theory and practice of design, 2025)
The article examines the use of essential oil, aromatic, and medicinal plants in the design of green spaces. The study aims to identify their aesthetic potential, phytoncidal properties, and possibilities for harmonious integration into urban and private landscaping. The objective is to justify the feasibility of using essential oil, aromatic, and medicinal plants in modern green space design as elements combining decorative, ecological, and health-promoting functions. Purpose. The purpose of the study is to justify the feasibility of using essential oil, aromatic, and medicinal plants in modern green space design as elements that combine decorative value, ecological benefits, and health-promoting effects. Methodology. A comprehensive approach was applied, including the analysis of scientific sources on phytodesign, botany, and landscape architecture, a comparative-descriptive method to study morphological and decorative plant traits, and a systematization method to determine principles for species selection based on their functional purpose. Ecological-aesthetic criteria, seasonal flowering dynamics, and aromatic compositional compatibility of species were considered. Results. It was established that essential oil, aromatic, and medicinal plants, besides their decorative value, enhance air quality, create a favorable microenvironment, and positively influence human psycho-emotional state. The use of species such as narrow-leaved lavender (Lavandula angustifolia), medicinal sage (Salvia officinalis), common thyme (Thymus vulgaris), lemon balm (Melissa officinalis), rosemary (Rosmarinus officinalis), calendula (Calendula officinalis), peppermint (Mentha piperita), among others, allows the creation of functional-decorative gardens, aromatic alleys, and therapeutic recreational areas. Scientific novelty. For the first time, approaches to using plants with high essential oil content in green space design are generalized from the perspective of their phytoncidal activity, coloristics, texture, and aroma. Principles for creating aromatic compositions are defined, combining plants’ bioenergetic properties with artistic-spatial solutions. Practical relevance. The results can be applied in the design of park and garden areas, creation of phytotherapeutic and relaxation zones, landscaping of sanatorium-resort facilities, and private gardens. The proposed recommendations contribute to the formation of ecologically sustainable, aesthetically expressive, and health-promoting green spaces.